KEMAMPUAN INOVASI PERUSAHAAN DI INDUSTRI PERCETAKAN DALAM MEMPERTAHANKAN BISNIS PASCA PANDEMI COVID-19 (STUDI PENDEKATAN GROUNDED THEORY TERHADAP CV DUMMY SOLID) - Mila Herfina; Azwar; Nidia Sofa (EPIGRAM (e-journal), 2022)
This study aims to determine the company's innovation ability in maintaining business after the COVID-19 pandemic with a grounded theory approach. This study uses a qualitative research method with a grounded theory approach as a model in the study. Researchers collected data using semi-structured interviews, field observations, document analysis, and literature studies. The results obtained by researchers are that the COVID-19 pandemic has greatly impacted the economy of CV Dummy Solid's company, the COVID-19 pandemic has become something that suppresses and threatens the survival of the company. The impacts experienced by companies due to the COVID-19 pandemic include financial losses, reduction in the number of employees, rolling employees, delays in giving bonuses, reduced production quantities, and savings in raw materials. By conducting a SWOT analysis and researching with a grounded theory approach, it was found that the company's innovation was the company's strategy to survive the COVID-19 pandemic. When the innovation is successfully carried out by CV Dummy Solid, then CV Dummy Solid is considered to have the ability to innovate. From this grounded theory approach, a new understanding can be found: “The company's innovation ability arises because of pressure from the COVID-19 pandemic, which then arises because of this opportunity and strength from companies that are used to survive during the COVID-19 pandemic".